Discrimination between aflatoxigenic and non-aflatoxigenic Aspergillus section Flavi strains from Egyptian peanuts using molecular and analytical techniques - Abdel-Hadi, Ahmed; Carter, David; Magan, Naresh (Wageningen Academic Publishers, 2011)
A wide range of Aspergillus section Flavi strains were isolated from Egyptian peanut samples. Eighteen of these strains were compared with two type strains (Aspergillus flavus SRRC G1907 and Aspergillus parasiticus 2747) for aflatoxin production based on (a) qualitative fluorescence using a coconut cream agar medium (CAM), and (b) aflatoxin production on a conducive Yeast Extract-Sucrose (YES) medium using HPLC. These results were validated by using molecular approaches (the structural genes, aflD (nor-1), aflM (ver-1) and aflP (omt A) and the regulatory gene aflR) to discriminate between aflatoxigenic and non- aflatoxigenic strains of the Aspergillus section Flavi group in vitro and on peanut seeds. Overall, 13/18 strains producing aflatoxins B1 and B2 in the range 1.27-213.35 µg/g medium were identified. In addition, 5 non-aflatoxin producing strains were found. The expression of these four genes was assessed using PCR and RT-PCR. PCR showed that all strains contained the four aflatoxin genes examined, regardless of expression profiles. Our results also showed that aflD expression is a reliable marker to discriminate between aflatoxin and non- aflatoxin producers. Interestingly, when an aflatoxin producing strain and three non-aflatoxigenic strains were subsequently grown on peanuts at 0.95 water activity, two of the non-producers were able to initiate aflatoxin biosynthesis. This suggests that growth of strains on the natural food matrix is important for confirming aflatoxigenic production potential